Functional expression of two Bacillus subtilis chromosomal genes in Escherichia coli. - Chi, N Y (1978)
EcoRI-cleaved deoxyribonucleic acid segments carrying two genes from Bacillus subtilis, pyr and leu, have been cloned in Escherichia coli by insertion into a derivative of the E. coli bacteriophage lambda. Lysogenization of pyrimidine- and leucine-requiring auxotrophs of E. coli by the hybrid phages exhibited prototrophic phenotypes, suggesting the expression of B. subtilis genes in E. coli. Upon induction, these lysogens produced lysates capable of transducing E. coli pyr and leu auxotrophs to prototrophy with high frequency. Isolated DNAs of these bacteriophages have the ability to transform B. subtilis auxotrophs to pyr and leu independence and contain EcoRI-cleaved segments which hybridize to corresponding segments of B. subtilis.